The complete mitochondrial genome of Cynoglossus joyneri (Teleostei: Pleuronectiformes). Issue 1 (1st January 2016) - Ren, Li-Hua; Xu, Tao; Sun, Guo-Hua; Li, Fan; Wang, Wei-Jun
Abstract: The complete mitochondrial genome of a commercially important sea fish Cynoglossus joyneri was sequenced and annotated. The 16, 941 bp-long genome contained 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs, and a control region. Phylogenetic analysis indicated that C. joyneri is a sister group with C. sinicus and C. bilineatus, and corroborated the proposed paraphyly of Cynoglossus genus.